Khwadāynāmag : the Middle Persian Book of kings - Hameen-Anttila, Jaakko. (Studies in Persian Cultural History, 2018)
Khwadāynāmag. The Middle Persian Book of Kings by Jaakko Hämeen-Anttila analyses the lost sixth-century historiographical work of the Sasanians, drawing on a large number of Middle Persian, Greek, Arabic, and Classical Persian sources. The Khwadāynāmag is often conceived of as a large book of stories, comparable to Firdawsī's Shāhnāme , but Hämeen-Anttila convincingly shows that it was a concise and dry chronicle. He also studies the lost Arabic translations of the book, which turn out to be fewer than hitherto thought, as well as the sources of Firdawsī's Shāhnāme , showing that the latter was only remotely related to the Khwadāynāmag . It also becomes clear that there were no separate \'priestly\' and \'royal\' Khwadāynāmags .